Predictors of Protective Behaviors Against Sexually Transmitted Infections in Women of Reproductive Age - Derya Dağdelen; Handan Zincir (Turkish Journal of Family Medicine and Primary Care, 2026)
Objective:In this study, the levels of sexual self-efficacy and protective behavior against sexually transmitted infections among women of reproductive age and the factors associated with protective behavior against sexually transmitted infections were explored.Methods:The study data were collected online via Google Form between April and June 2024. Descriptive Characteristics Form, Sexual self-efficacy (SSE) Scale, and Behavior Scale for Protection from Sexually Transmitted Diseases(STD-SCS) were used to evaluate the participants. The research was completed with 494 women. Data were analyzed using multiple linear regression analyses (enter method).Results:In this study, the participants’ mean STD-SCS and SSE scores were 83.9 (SD=10.9) and 32.6 (SD=7.1), respectively. The mean SSE scale scores and sociodemographic characteristics of the participants were identified as significant determinants of the mean STD-SCS scores. In addition, education level, sexual self-efficacy, and knowledge about sexually transmitted diseases were found to be significant factors influencing protective behaviors.Conclusions:To ensure that no one is left behind, programs to improve women's sexual self-efficacy should be included in clinical/field intervention programs to be carried out for the prevention of sexually transmitted infections.